Peran Guru dan Orang Tua dalam Pendidikan Karakter untuk Mengatasi Dekadensi Moral Anak: Literature Review - Nurhayati, Desti; Ekasari, Isnaini Yuliana Ekasari; Ani, Rosa Nur Ani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The presence of parents and teachers has a crucial role in shaping children's character to overcome moral decadence. Through literature reviews of various articles and books and using data analysis techniques in the form of content analysis so that this research is carried out by selection, comparison, and combination so that what is found is relevant. This research analyzes the contribution of parents and teachers to character education. The results show that positive interactions, open communication, and good examples from parents can increase moral values in children. Apart from that, the role of teachers in the formal education environment is also very important. A holistic character education program for children at school can provide a strong foundation for children to develop children's ethics, a sense of responsibility and empathy. This research can explain that effective collaboration between parents and teachers can be an effective solution in facing the challenge of children's moral decadence